Pemanfaatan Teknologi Informasi untuk Mempermudah Pencatatan dalam Laporan Keuangan UMKM - Yulianto Yulianto; Lyandra Aisyah Margie; Afridayani Afridayani (Universitas Pamulang, 2021)
The purpose of this Community Service activity is to carry out one of the Tri Dharma of Higher Education and the main goal is to provide solutions to problems faced by Micro, Small and Medium Enterprises (MSMEs), especially in the MSMEs of the Asri Berseri Garbage Bank. In addition, it is hoped that with this community service, the existence of universities can make a major contribution to the development and application of science to the community. The method used in this service is by way of counseling and training in the form of seminars and also field assistance in order to get a solution to the problems faced by MSME business actors. The results of this community service are in the form of knowledge and understanding of how to make financial reports in accordance with SAK EMKM standards. The knowledge gained in Community Service this time is expected to be able to provide new enthusiasm for lecturers in an effort to develop themselves in providing direction, delivery of material and motivation as well as contributing to the development of the business world, especially the MSME sector both around the campus and nationally.